Online Health Information Seeking for Self and Child: An Experimental Study of Parental Symptom Search - Christian Kubb; Heather M Foran (JMIR Publications, 2022)
BackgroundParents often search the web for health-related information for themselves or on behalf of their children, which may impact their health-related decision-making and behaviors. In particular, searching for somatic symptoms such as headaches, fever, or fatigue is common. However, little is known about how psychological and relational factors relate to the characteristics of successful symptom-related internet searches. To date, few studies have used experimental designs that connect participant subjective search evaluation with objective search behavior metrics. ObjectiveThis study aimed to examine the features of web-based health-related search behaviors based on video-coded observational data, to investigate which psychological and relational factors are related to successful symptom search appraisal, and to examine the differences in search-related outcomes among self-seekers and by-proxy seekers. MethodsIn a laboratory setting, parents living in Austria (N=46) with a child aged between 0 and 6 years were randomized to search their own (n=23, 50%) or their child's (n=23, 50%) most recent somatic symptom on the web. Web-based activity was recorded and transcribed. Health anxiety, eHealth literacy, attitude toward web-based health information, relational variables, state of stress, participants' search appraisals, and quantitative properties of the search session were assessed. Differences in search appraisals and search characteristics among parents who searched for themselves or their children were examined. ResultsAcross both groups, searches were carried out for 17 different symptom clusters. Almost all parents started with Google (44/46, 96%), and a majority used initial elaborated key phrases with >1 search keyword (38/45, 84%) and performed on average 2.95 (SD 1.83) search queries per session. Search success was negatively associated with health anxiety (rs=−0.39, P=.01), stress after the search (rs=−0.33, P=.02), and the number of search queries (rs=−0.29, P=.04) but was not significantly associated with eHealth literacy (rs=0.22, P=.13). Of note, eHealth literacy was strongly and positively correlated with satisfaction during the search (rs=0.50, P<.001) but did not significantly correlate with search characteristics as measured by search duration (rs=0.08, P=.56), number of performed search queries (rs=0.20, P=.17), or total clicks (rs=0.14, P=.32). No differences were found between parents searching for their own symptoms and parents searching for their child's symptoms. ConclusionsThis study provides exploratory findings regarding relevant dimensions of appraisals for symptom-based information seeking on the web. Consistent with previous literature, health anxiety was found to be associated with poorer search evaluation. Contrary to expectations, eHealth literacy was related neither to search success nor to search characteristics. Interestingly, we did not find significant differences between self-seekers and by-proxy seekers, suggesting similar search and evaluation patterns in our sample. Further research with larger samples is needed to identify and evaluate guidelines for enhanced web-based health information seeking among parents and the general public.